Polygyrid land snails, Vespericola (Gastropoda: Pulmonata), 4. A new and possibly extinct species from central California, U.S.A. - Roth, Barry (Zootaxa, 2003)
Vespericola ohlone sp. nov., is described from material collected in the nineteenth century, probably around freshwater marshes in Alameda County, central California. No more recent collecting records have been found, and the species may be extinct. The new species differs from Vespericola pilosus (Henderson, 1928) in having its base produced and somewhat excavated around the umbilicus, the inner quadrant of the base with a small shelf set off by a spiral sulcus behind the basal lip, and the inner part of the basal lip angled, rather than gently curved, forward. The soft anatomy is unknown.